A fully compensated ferrimagnetic half metal Co1-xCrxS2 with Curie temperature above room temperature - Venkatesan, Munuswamy; Coey, John (My University, 2023)
Fully compensated ferrimagnetic half metals have attracted great attention in spintronics. Unlike many previous calculations based on hypothetical ordered alloys, here we look for existing solid solution series taking as an example Co1−xCrxS2. Calculations find that a low-spin state for Cr that matches early experiments and a fully compensated ferrimagnetic half metal with Curie temperature above room temperature is found at x ≈ 0.33. Our study demonstrates the method of combining two half metals with light and heavy 3d metals in a solid solution to achieve compensation, where atomic disorder does not destroy the desired properties.
PUBLISHED
Keywords: Nanoscience & Materials; Applied physics; Condensed matter, electronic, magnetic and superconductive properties; Magnetism and spin electronics; Nanotechnology; Education